English The Existence of Muhadharah’s Extracurricular and Its Relevance in The Forming of Student’s Confidence in MA Fadllillah Sidoarjo - M. Chanif Nasich; Noris Firmansyah; A. Fikri Amiruddin Ihsani; Novi Febriyanti (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2023)
This study discusses the existence of Muhadharah's extracurricular and its relevance in building the self-confidence at MA Fadllillah Sidoarjo students. The focus of the problem in this study is how the implementation of Muhadharah's extracurricular and its relevance in building the self-confidence at MA Fadllillah Sidoarjo students. The purpose of this study was to identify, describe, and analyze the implementation of Muhadharah's extracurricular and its relevance in building the self-confidence at MA Fadllillah Sidoarjo students. The research method used in this study is a qualitative research method with descriptive analysis. In this study, it was found that the implementation of Muhadharah's extracurricular was very relevant to be used as a self-confidence formation at MA Fadllillah Sidoarjo students. This is done by several things, including regular and continuous training of Muhadharah, support and motivation from supervisors, as well as giving rewards after daring to display their abilities in public.